A case of spontaneous pneumomediastinum, pneumothorax with subcutaneous emphysema in a preschool child - Parihar, Rashmi; Shrivastav, Abhijat K.; Ashokan, Vishakha; K. P., Malini (International Journal Of Community Medicine And Public Health, 2023)
Spontaneous subcutaneous emphysema is the presence of gas or air beneath the skin and soft tissues. Pneumothorax and pneumomediastinum are identified by the existence of free gas or air in the associated spaces. 4-year-old with progressive body swelling of 12-hour duration, started just after nebulisation with bronchodilators prescribed for his cough and cold. Examination revealed conscious, anxious, irritable child and obvious superficial swelling of face, scalp, neck, chest and both upper limbs. tachycardia, tachypnoea and his oxygen saturation were 82% at the time of admission. There was crepitus on palpation. Investigations were done; A diagnosis of spontaneous pneumomediastinum, left pneumothorax with spontaneous subcutaneous emphysema was made. Managed with emergency implantable cardioverter-defibrillator (ICD) insertion, oxygen, intravenous antibiotics, intravenous fluids, analgesics, and nebulisation.